THUR 153 Antibodies against the voltage-gated potassium channel complex. Issue 10 (13th September 2018) - Das, Joyutpal; Chauhan, Vanisha; Keh, Ryan; Mills, Daniel; Nicholas, Johal; Matthews, Rachael; Lilleker, James; Gosal, David; Sharaf, Nazar
Abstract : Voltage-gated potassium channel (VGKC) complex antibodies have been associated with a spectrum of presentations including peripheral nerve hyperexcitability (PNH), Morvan's syndrome, autoimmune encephalopathy, epilepsy and recently psychosis. We retrospectively reviewed the medical records of 70 patients from the Greater Manchester Neuroscience Centre, who had tested positive for VGKC-complex antibodies between 2012 and 2015 to identify the clinical relevance of positive results. The majority were diagnosed with autoimmune encephalopathy(19) followed by epilepsy(14), psychosis(10) and PNH(6). The remaining fifteen had other neurological presentations and six had no primary neurological disorder. 39/70 patients who had antibody titres>400 pM, were diagnosed with autoimmune encephalopathy(19), epilepsy(9), psychosis(4), PNH(3) and other disorders(4). 24/39 patients, who received treatment with one or a combination of corticosteroids, intravenous immunoglobulins, cyclophosphamide, plasma exchange, azathioprine or rituximab, had a diagnosis of autoimmune encephalopathy(18), epilepsy(2), psychosis(2) and malignancy(2). 16/24 were treatment responsive. 3/31 patients with lower titres were also treated, but only one with the classic phenotype (PNH) responded to treatment. The classic phenotype often had a titre >400 pM. PNH may have a titre ≤400 pM. The patients without classic presentations typically had titres≤400 pM. Consistent with previous studies, clinical phenotyping and antibody titre helped to determine the relevance of VGKC-complex antibodies.